2018
DOI: 10.5582/bst.2018.01082
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufacini inhibits epithelial-mesenchymal transition of human hepatocellular carcinoma cells through c-Met/ERK signaling pathway

Abstract: Cinobufacini, an aqueous extract from the skins and parotid venom glands of the toad Bufo bufo gargarizans Cantor, is a well known traditional Chinese medicine widely used in clinical cancer therapy in China. Its therapeutic effect is especially pronounced in liver cancer. However, the precise mechanisms induced by cinobufacini in human hepatocellular carcinoma (HCC) cells are still not very clear. Here, we investigated the effects and mechanisms of cinobufacini on inhibiting HepG2 cells invasion and metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For example, deguelin can suppress tumor angiogenesis on vascular endothelial cells by decreasing autocrine VEGF and repressing HGF-induced c-Met signaling pathways, thereby inhibiting HCC progression . Also, Cinobufacini, a well-known traditional Chinese medicine extracted from toad skins and venom glands, has a therapeutic effect in HCC (Qi et al, 2018). A study has found that Cinobufacini could suppress HepG2 cell invasion and metastasis through the inhibition of the c-Met/ERK induced EMT (Qi et al, 2018).…”
Section: Natural Compound and Herbal Medicinesmentioning
confidence: 99%
“…For example, deguelin can suppress tumor angiogenesis on vascular endothelial cells by decreasing autocrine VEGF and repressing HGF-induced c-Met signaling pathways, thereby inhibiting HCC progression . Also, Cinobufacini, a well-known traditional Chinese medicine extracted from toad skins and venom glands, has a therapeutic effect in HCC (Qi et al, 2018). A study has found that Cinobufacini could suppress HepG2 cell invasion and metastasis through the inhibition of the c-Met/ERK induced EMT (Qi et al, 2018).…”
Section: Natural Compound and Herbal Medicinesmentioning
confidence: 99%
“…EMT is an important biological process induced by the c-met signaling pathway and is a crucial initiation step required for tumor migration and invasion [ 49 ]. MMPs, which are major proteolytic enzymes, have an important role in the degradation of the extracellular matrix, and thus, contribute to the regulation of tumor metastasis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is an important biological process induced by the c-met signaling pathway and is a crucial initiation step required for tumor migration and invasion [ 49 ]. MMPs, which are major proteolytic enzymes, have an important role in the degradation of the extracellular matrix, and thus, contribute to the regulation of tumor metastasis [ 49 ]. In the current study, silencing of FASN, FSCN1 or SPTBN1 expression in liver cancer cells led to changes in the mRNA expression of EMT-associated markers, E-cadherin, N-cadherin, vimentin and transcription factors Snail and Twist, and altered the protein expression of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…HGF‐induced C‐MET–dependent signal transduction promoted PKM2 nuclear translocation, and the nuclear translocation of PKM2 directly determined C‐MET–dependent cell proliferation. ERK 1/2 is an important downstream molecule for signal transduction after C‐MET activation, and it is also upstream of PKM2 in EGFR activation‐induced glioblastoma growth . Previous studies have demonstrated that EGFR‐mediated ERK1/2 activation promotes PKM2 S37 phosphorylation that determines PKM2 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%